2020
DOI: 10.1021/acs.organomet.9b00816
|View full text |Cite
|
Sign up to set email alerts
|

Determining the Catalyst Properties That Lead to High Activity and Selectivity for Catalytic Hydrodeoxygenation with Ruthenium Pincer Complexes

Abstract: Ten ruthenium pincer complexes were evaluated as catalysts for the hydrodeoxygenation (HDO) reaction on a lignin monomer surrogate, vanillyl alcohol. Four of these complexes are reported herein with the synthesis and full characterization data for all and single-crystal X-ray diffraction data for three complexes bearing OH/O − , NMe 2 , and Me substituents on the pincer. A systematic study of these CNC pincer complexes revealed that the π-donor substituent on the pyridine ring plays a key role in enhancing the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 19 publications
(30 citation statements)
references
References 45 publications
1
24
0
Order By: Relevance
“…In a more recent work, the same group employed a series of pincer analogs of 19 to catalyze the hydrodeoxygenation of alcohols (Scheme 9). [20] It was revealed that 19 and analogs that bear pyridine π‐donor substituents (OMe, OH, NMe 2 ) are superior catalytic performers. This was rationalized by the proposal that a π‐donor substituent makes the Ru center more electron‐rich and thus weakens the ligated H−H bond in the transient intermediate B .…”
Section: Nhc Employed As An Arm Donormentioning
confidence: 99%
“…In a more recent work, the same group employed a series of pincer analogs of 19 to catalyze the hydrodeoxygenation of alcohols (Scheme 9). [20] It was revealed that 19 and analogs that bear pyridine π‐donor substituents (OMe, OH, NMe 2 ) are superior catalytic performers. This was rationalized by the proposal that a π‐donor substituent makes the Ru center more electron‐rich and thus weakens the ligated H−H bond in the transient intermediate B .…”
Section: Nhc Employed As An Arm Donormentioning
confidence: 99%
“…The syntheses of the ruthenium complexes, Ru OMe , Ru H , Ru OH , Ru NMe2 , and Ru Me , complexes, were reported recently by us. [4a], These complexes were studied as alcohol hydrodeoxygenation (HDO) catalysts. It was demonstrated by both spectroscopic and crystallographic methods that the oxygen and nitrogen substituents donate electron density towards the metal center and thereby enhance catalytic rates .…”
Section: Resultsmentioning
confidence: 99%
“…It was demonstrated by both spectroscopic and crystallographic methods that the oxygen and nitrogen substituents donate electron density towards the metal center and thereby enhance catalytic rates. [7] Furthermore, Ru OH is readily deprotonated by mild bases, which results in an even stronger π donor group and the most active HDO catalyst. However, the complexes Ru OH , Ru NMe2 , and Ru Me have not been studied for photocatalysis.…”
Section: Synthesismentioning
confidence: 99%
See 2 more Smart Citations